DAKWAH DI ERA CYBERCULTURE: PELUANG DAN TANTANGAN - Ishanan, Ishanan (Universitas Islam Negeri Mataram, 2017)
The development has happened yang outstanding in the field of communication technology. These developments certainly influence on Da’wah. In the context of the current Da’wah should have already started to greet the audiences through the mediamedia-art, among them with what is known by the term “new media”, which is marked by the birth of the internet, virtual reality, or a Cyber community, as a direct result of the development of telematics technology. Therefore, in this paper the author would like to see: How the culture takes place in the era of Cyberculture? Calling others what can be done in the era of Cyberculture? Like what is challenging da’wah in the era of Cyberculture.? At first, the virtual community is a human fantasy about another world that is ahead of the world today. The fantasy is a hyperreallity man about the value, imagery, and the meaning of human life as the emblem of the liberation of man against the powers of matter and the universe. But when human technology is able to reveal the mystery of that knowledge, then any man capable of creating spaces of new life for human beings in the world of hiperreality. In this context, then the perpetrators prosecuted for preaching not only adept at above the pulpit, but must also be proficient as a da’i provider. The advent of advanced technologies that offer convenience to society in the era of Cyberculture to preach. Therefore, the current required to its grads to use Media as a means of propagation are tailored to the characteristics of the information society.